Game on: immersive virtual laboratory simulation improves student learning outcomes & motivation - Tsirulnikov, Danielle; Suart, Celeste; Abdullah, Ream; Vulcu, Felicia; Mullarkey, Caitlin E. (FEBS open bio, 2023)
The use of gamified learning interventions is expanding in postsecondary education as a means to improve students' motivation and learning outcomes. Virtual laboratory simulations have been used in science education to supplement students' learning, as well as to increase engagement with course material. Due to COVID‐19, many instructors sought to replace or supplement hands‐on ‘wet‐lab’ work in an online environment. In this paper, we explored how the use of head‐mounted display technology in two laboratory simulations impacts learner motivation and learning outcomes. We used a mixed‐methods approach to analyze the experience of 39 undergraduate participants, examining test scores pre‐ and postsimulation, qualitative feedback, and quantitative experience ratings. The head‐mounted display technology was described as easy to use, with eye strain identified as a common occurrence. Participants had increased test scores following the laboratory simulations, with no significant difference between simulation groups. Very positive self‐reported measures of motivation and learner engagement were documented. Ninety‐one percent of participants agreed that virtual reality laboratory simulation would be a good supplement to regular teaching modalities. Overall, our results suggest that immersive virtual reality laboratory simulations experienced through head‐mounted display technology can be used to enhance learning outcomes and increase learner motivation. We examined how immersive virtual reality laboratory simulations impact learner motivation and learning outcomes. Our results demonstrate that learners had increased test scores and very positive self‐reported ratings of motivation after simulation completion. Learners found the technology intuitive, although eye strain was reported. We identify best practices for implementation and suggest how simulations could supplement traditional laboratory teaching modalities.